PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA BISNIS BANK UMUM SYARIAH (BUS) DI INDONESIA - Taat Khasan; Minadi WIjaya; Sully Kemala Octisari (Majalah Imiah Manajemen & Bisnis, 2020)
This study In order to survive, companies must quickly change its strategy labor-based business towards knowledge based business, so that the main characteristics of the company because a science-based company. One approach used in the assessment is the measurement of knowledge assets (knowledge assets) is Intellectual Capital.. This research tested the effecetof three components of VAIC™ (Value Added Intellectual Coefficient): VAHU (Value Added Capital Employeed), VACA (Value Added Human Capital), and STVA (Sructure Capital Value Added) to the sharia banking bussines performance (profit sharing ratio). Data obtained from the nine sharia commercial bank in Indonesia during the four-year period from 2014 to 2017. The number of samples used were 36 financial annual reports . The study's findings indicate value added capital employed (VACA) have significant impact, while value added human capital (VAHU) and stuctural capital value added (STVA) not having significant impact about the sharia banking bussines performance in Indonesia.